Reconstructing and re-defining the space: Living in between the slum and the tourist destination - Manggala Ismanto; Irsyad Martias; Reza Sutowo; Rizal Noviar (Faculty of Social and Political Science, Universitas Airlangga, 2019)
Efforts to reconstruct landscapes and living spaces occur in cities, especially in urban slums. This effort is not only carried out by the settlers but also by external actors who have the intention to improve their lives. It is interesting to see the encounter between actors, especially regarding how negotiations occur between their interests. Jodipan Village becomes one of the slums areas in Malang which make efforts to define and reconstruct the space of their living space by re-colouring the neighbourhood landscape. By the collaboration of various stakeholders such as private parties and the civil society, the village space redefined into a tourist destination that attracts tourists to visit. We gathered a set of information from six local people, one public official, and two team members of Guyspro. Nowadays, Jodipan is popularly known as Kampung Warna-Warni Jodipan or Jodipan Colorful Village (KWJ). The spatial changes which rise from the grass-root provide the opportunities and challenges for the community to negotiate the process of the urban planning implementation in Malang. As a result, the slum stigma has been alleviated and the public acknowledgements that Jodipan Village is being a tourist destination, giving a chance to the settlers to gain their right to live in Jodipan Village area. With this thematic village, the community learns to manage their assets independently by creating a management team that manages the printing of ticket passes, repainting and organising parking lots that benefit local people.